History in Public: Power and Process, Harm and Help. - Romein, Christel Annemieke; Doak, Laura; Parker, Hannah; Weston, Janet (History, 2022)
This introductory piece explains the choice of public history as a focus for this special issue of History, and its emphasis on the work of early‐career historians. 'Public history' is a notoriously nebulous concept. We outline some of the most common ways in which it is understood, and discuss why we believe that its methods and approaches are of enormous value to all those involved in historical work, whether they would consider themselves to be 'public historians' or not. We also introduce the contributions making up the rest of this issue, which features the work of twenty‐five mostly early‐career historians and moves from Greece to England, India, Tobago, the United States, Norway, Northern Ireland, and online. The introduction provides an appetiser for some of the approaches, ideas and struggles emerging from public history, and the richness of this constantly evolving field.